Wetland landscape characterization practical tools, methods, and approaches for landscape ecology - Lopez, Ricardo D. (CRC Press, 2013)
"Preface Decision makers of all types are increasingly called upon to determine the details of the complex and transitional ecosystem called "wetlands." Because wetlands are, by their very nature, ephemeral and transitional, their complexity makes the task of capturing their essence, that is, characterization, very challenging. The need for characterizing wetlands is growing every day to meet scientific and societal needs, and this need is on the increase as we better understand the wealth of ecosystem services wetlands provide us all. For those continuing their quest for wetland knowledge, this second edition of Wetland Landscape Characterization is designed to enhance their knowledge base, providing them with a pathway to understanding how wetland characterization tools, methods, and approaches can be integrated to address twenty-first-century wetland issues"-- Provided by publisher.
Keywords: Wetland ecology.; elektronické knihy; electronic books